Maintaining The Leading Economy of The City of Semarang - Asnita Frida Sebayang; Lesta Karolina Sebayang; Cecep Fauzan Al Rifah (Economics Development Analysis Journal, 2024)
The economic position of a city is crucial for the sustainability of regional economic development. To enhance competitiveness and achieve economic excellence, a combination of simultaneous drivers is necessary. As the core city of the Kedungsepur agglomeration, Semarang City plays a strategic role in regional development. This study employs a quantitative methodology, utilizing the Location Quotient (LQ) technique with data sourced from the Central Bureau of Statistics (BPS). The findings indicate that Semarang City's economic transformation, characterized by competitiveness and specialization in the trade, real estate, and public service sectors, requires support from surrounding regions to maximize its role in driving sustainable economic growth. Additionally, the study identifies the city's prime sectors—trade, real estate, public services, and transportation and warehousing—highlighting their contribution to generating high-added value amid global economic dynamics. Despite its economic diversification, Semarang City remains heavily reliant on the manufacturing industry due to its substantial sectoral contribution. Therefore, while manufacturing remains a key pillar of the local economy, identifying new growth potentials and fostering collaborative strategies within the agglomeration area is essential for long-term economic resilience. Semarang City possesses significant potential for sustainable growth by distributing the benefits of development to its surrounding regions, reinforcing its role as a regional economic driver.